Qualitative insights on sexual health counselling from refugee youth in Bidi Bidi Refugee Settlement, Uganda: Advancing contextual considerations for brief sexuality-related communication in a humanitarian setting - Loutet, Miranda G.; Logie, Carmen H.; Okumu, Moses; Coelho, Madelaine; Blondeel, Karel; McAlpine, Alyssa; Mackenzie, Frannie; Lukone, Simon Odong; Kisubi, Nelson; Lukone, Jimmy Okello; Isaac, Atama Malon; Kyambadde, Peter; et al. (PloS one, 2024)
Characteristics of enabling healthcare environments to support brief sexuality-related communication (BSC) are understudied in humanitarian settings. We implemented a qualitative study with refugee youth aged 16–24 living in Bidi Bidi Refugee Settlement to understand the feasibility of implementing BSC in a humanitarian context. We examined feelings toward doctor’s visits in general, including types of conversations youth engage in with healthcare providers, as well as comfort, safety, and willingness to talk with healthcare providers about sexual health. We implemented four focus groups with refugee youth in Bidi Bidi, two with young women and two with young men, and applied thematic analysis informed by a social contextual theoretical framework that explores enabling environments for sexual health promotion. Participants (n = 40; mean age: 20 years, standard deviation: 2.2; women: n = 20; men: n = 20) reported relational, symbolic, and material dimensions of context considered important when discussing sexual health. Relational contexts included a) trusting relationship with local healthcare practitioners, including practices that foster comfort and confidentiality, and b) family, friends, and mentors as additional sources of health information. Symbolic contexts refer to values, norms, and beliefs that reflect what is perceived as valuable and worthy, and in turn, what is devalued and stigmatized. Specific to sexual health, participants discussed stigma toward STIs and HIV, devaluation of women in healthcare settings, and generalized fear of doctors and disease as barriers to engaging in dialogue about sexual health with healthcare providers. Material contexts include agency linked with resource access and experiences. Youth narratives revealed that positive experiences accessing medication to manage pain and infections increased their willingness to engage in healthcare discussions, whereby clinic layouts and dynamics that compromised confidentiality and privacy reduced the likelihood of sexual health dialogue. Language barriers and healthcare provider time constraints were additional factors that reduced healthcare engagement. Taken together, findings can inform BSC implementation strategies that consider the inner and outer settings that shape sexual health dialogue and sexual health and wellbeing among refugee youth living in humanitarian settings.